Aging Behavior of Reactive Air Brazed Seals for SOFC1. Issue 5 (3rd August 2015) - Pönicke, A.; Schilm, J.; Kusnezoff, M.; Michaelis, A.; Christiansen, Niels; Hagen, Anke; Bele, Petra; Bucheli, Olivier
Abstract In this study the gas‐tightness of reactive air brazed YSZ‐steel joints and their long‐term stability at high temperatures in air and dual atmospheres are investigated. Silver‐based braze compositions like Ag‐4CuO are used for reactive air brazing of gas‐tightness samples. During aging in air at 850 °C for 800 h all tested samples remained hermetic. However, microstructural analysis reveals the formation of voids within the brazing zones and severe changes of the interfacial oxide layers. It is shown, that due to the diffusion of chromium and manganese from the steel substrate the thickness of the reaction layers increases and the phase composition changes. Furthermore, in previous work a decrease of the bending strength of reactive air brazed YSZ‐steel joints due to the microstructural changes is observed. In contrast, the aging in dual atmospheres at 850 °C causes strong degradation and the total loss of gas‐tightness. Reducing atmospheric conditions lead to different reactions profiles of the silver based brazes in contact with the YSZ electrolyte. Complex reaction products are identified and reported.